A red emitting of manganese-doped boron carbon oxynitride (BCNO) phosphor materials: facile approach and photoluminescence properties. Issue 7 (17th January 2017) - Nuryadin, Bebeh W.; Permatasari, Fitri A.; Nuryantini, Ade Y.; Faryuni, Irfana D.; Abdullah, Mikrajuddin; Iskandar, Ferry
Abstract : A bright red emission of manganese-doped BCNO (BCNO:Mn) phosphor was firstly synthesized by solid state method. Abstract : BCNO (boron carbon oxynitride) phosphors have attracted attention due to their non toxicity, simple synthesis process, and high quantum efficiency. However, the tunable emission, particularly a red emission, is still challenging to achieve. In the present study, a bright red emission (emission wavelength 620 nm under 365 nm UV excitation) of a manganese-doped BCNO (BCNO:Mn) phosphor synthesized by a solid state method is reported. Without Mn-doping, the BCNO phosphor exhibited a bright blue emission that can be ascribed to the closed-shell BO − and BO 2− anions that act as luminescence center. Via Mn-doping, a red emission was exhibited that can be ascribed to the 4 T1 ( 4 G) → 6 A1 ( 6 S) transition from a new luminescence center of Mn 2+ incorporated into the BCNO host lattice. The optimum red PL properties ( λ em : 611 nm, λ ex : 365 nm) were obtained with BCNO:Mn at a molar ratio of Mn/B at 0.71% mol/mol synthesized at 550 °C. We believe that the BCNO:Mn is a promising red-emitting phosphor for white light diodes.